Correction: Paper-based molecular diagnostic for Chlamydia trachomatis. Issue 77 (22nd August 2015) - Linnes, Jacqueline C.; Fan, Andy; Rodriguez, Natalia M.; Lemieux, Bertrand; Kong, Huimin; Klapperich, Catherine M.
<x xml:space="preserve">Abstract</x> Correction for 'Paper-based molecular diagnostic for Chlamydia trachomatis' by Jacqueline C. Linnes et al., RSC Adv., 2014, 4, 42245–42251.